Exploring the positive impacts of social media engagement among Malaysian secondary school students - Ismail, Halim; Mamat, Arifin; Ibrahim, Hasniza; Mokhtar, Nazatul Akmar; Zailan, Muhammad Noor aiman (Scientific Research Publishing, 2025)
This study explores the positive impact of social media engagement on character development among Malaysian secondary school students. Employing a qualitative approach, data were collected through interviews with eight secondary school students from various backgrounds. The findings reveal that when navigated purposefully, social media use significantly contributes to a) students’ ability to learn independently, b) build meaningful social relationships, and c) enhance their communication skills. The subthemes for independent learners are 1) goal-oriented, 2) intrinsically motivated, 3) independent learning, 4) reflective thinking, 5) adaptability, 6) lifelong learning orientation and 7) futureoriented learning engagement. The sub-themes for social relationships are 1) strengthening family ties, 2) enhancing peer relationships, and 3) improving teacher-student rapport. As for the communication skills, the sub-themes found are 1) increased confidence, 2) role modelling, 3) communication platform preference and 4) development of social initiative and engagement. These insights underscore the constructive potential of social media in shaping student character and suggest implications for educators, parents, and policymakers to promote positive and educational content in digital spaces actively